2021
DOI: 10.1371/journal.pone.0251734
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal birth weight with the risk of low birth weight and small-for-gestational-age in offspring: A prospective single-center cohort study

Abstract: Background Although low birth weight in Japan has slightly increased over the past several decades, the association between maternal birth weight and pregnancy outcomes remains poorly understood. Methods In this hospital-based, prospective cohort study conducted at the National Center for Child Health and Development, we obtained information on pregnant women’s birth weight via their maternal and child health handbook. We analyzed 944 women born at term after dividing them into five categories according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…Current differences in health statuses among prefectures can lead to differences in health statuses in subsequent generations. It has been suggested that lower maternal birth weight is associated with low-birth-weight infants in Japan [48]. Therefore, health guidance not only for middle-aged or older women with obesity but also for younger women with obesity might also be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Current differences in health statuses among prefectures can lead to differences in health statuses in subsequent generations. It has been suggested that lower maternal birth weight is associated with low-birth-weight infants in Japan [48]. Therefore, health guidance not only for middle-aged or older women with obesity but also for younger women with obesity might also be needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, data on the mother's delivery weeks were not collected in the JECS. With reference to previous studies, MBW was classified into five categories as follows: < 2,500 g, 2,500-2,999 g, 3,000-3,499 g, 3,500-3,999 g, and ≥ 4,000 g. 28,31 MBWs of < 500 g or > 6,000 g were treated as improbable data in this study. 10,32 Definition of PTD, early PTD, and late PTD Information on delivery week was transcribed from medical records in this study.…”
Section: Mbwmentioning
confidence: 99%
“…MBW, the main study exposure, was categorized into five groups as previously described, 28 with detailed characteristics shown in Table 2. The proportions of PTD, early PTD, and late PTD were higher among participants with an MBW < 2,500 g than among those with an MBW of 3,000-3,499 g. As MBW decreased, there were higher proportions of underweight participants and lower proportions of obese participants.…”
Section: Characteristics Of Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WHO describes low birth weight as a birth weight of <2,500 g regardless of the gestational age, and it continues to be a major public health issue globally with several short and long-term adverse outcomes ( 3 ). Low birth weight incorporates both premature births (a birth of newborns before 37 weeks of gestation) and small for gestational age (birth weights less than 10 th percentile for newborns of the same gestational age) ( 4 6 ). It can be caused by premature birth or the neonate being small for gestational age or both ( 5 ).…”
Section: Introductionmentioning
confidence: 99%